Success and failure in the incorporation of gold nanoparticles inside ferri/ferrocyanide thermogalvanic cells - Hassan A.H. Alzahrani; Mark A. Buckingham; Frank Marken; Leigh Aldous (Electrochemistry Communications, 2019)
Thermogalvanic systems represent a means to convert a temperature gradient into electricity, using only redox chemistry. However, the kinetics of electron transfer and physical mass transport of the redox couples are known limitations. In this study we present self-contained gelled thermogalvanic cells (or thermocells) containing the ferricyanide/ferrocyanide redox couple, which additionally have gold nanoparticles either immobilised at the gel/electrode interface, or distributed throughout the entire gel. Both methods of introducing the gold nanoparticles result in an apparent electrocatalytic improvement, as demonstrated by significant decreases in the electron transfer resistance. However, when used as thermogalvanic cells, only minor improvements were observed in power generation, and relatively rapid dissolution of the gold nanoparticles was observed, to yield passivating gold analogues of Prussian blue. Therefore successful preparation and short-term improvements have been demonstrated, but are offset by long-term stability issues. The relatively surprising instability of the generally inert gold nanoparticles in the presence of ferricyanide/ferrocyanide, particularly under thermogalvanic conditions, is of particular note. Keywords: Thermoelectrochemistry, Thermogalvanic cells, Gold nanoparticles